2022
DOI: 10.1098/rspb.2021.2702
|View full text |Cite
|
Sign up to set email alerts
|

Large-herbivore nemabiomes: patterns of parasite diversity and sharing

Abstract: Amidst global shifts in the distribution and abundance of wildlife and livestock, we have only a rudimentary understanding of ungulate parasite communities and parasite-sharing patterns. We used qPCR and DNA metabarcoding of fecal samples to characterize gastrointestinal nematode (Strongylida) community composition and sharing among 17 sympatric species of wild and domestic large mammalian herbivore in central Kenya. We tested a suite of hypothesis-driven predictions about the role of host traits and phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…They found previously unreported families from some primates and that closely related primate species had greater parabiome similarity. Titcomb et al (2022) tested for associations between the nemabiome and host traits or phylogenetic relatedness across 17 species of sympatric mammalian herbivores in Kenya as well as assessed parasite-sharing networks among hosts. Key findings included 53% of the nemabiome dissimilarity among faecal samples explained by host species, significant congruence between host and parasite phylogenies, and that host gut morphology predicted nematode community composition.…”
Section: Parabiomementioning
confidence: 99%
See 3 more Smart Citations
“…They found previously unreported families from some primates and that closely related primate species had greater parabiome similarity. Titcomb et al (2022) tested for associations between the nemabiome and host traits or phylogenetic relatedness across 17 species of sympatric mammalian herbivores in Kenya as well as assessed parasite-sharing networks among hosts. Key findings included 53% of the nemabiome dissimilarity among faecal samples explained by host species, significant congruence between host and parasite phylogenies, and that host gut morphology predicted nematode community composition.…”
Section: Parabiomementioning
confidence: 99%
“…Additionally, they suggested that central host species (i.e. hosts that shared parasite species with many other hosts) could be targeted for management strategies where deworming these hosts might limit the spread of parasites to threatened wildlife (Titcomb et al , 2022).…”
Section: Parabiomementioning
confidence: 99%
See 2 more Smart Citations
“…Megafauna has been present in most of the world's terrestrial ecosystems since the mid Cenozoic and is expected to have shaped the evolution of many extant species (Galetti et al, 2018; Malhi et al, 2016; Smith et al, 2018; Titcomb et al, 2022). Since the Late Pleistocene, there has been a high extinction‐selectivity for megafauna, with the result that most contemporary terrestrial ecosystems are deprived of megafauna and the functions they provide (Malhi et al, 2016; Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%